RESPONS PRODUKSI TANAMAN JAGUNG (Zea mays L.) TERHADAP PEMANGKASAN DAUN BAGIAN BAWAH - Christian T. Rompas; Selvie Tumbelaka; Deanne A. Kojoh (Universitas Sam Ratulangi, 2018)
ABSTRACT The purpose of this research was to examine the response of the maize production towards lower leaves pruning. This research was conducted in Malalayang Satu Timur, Manado City, North Sulawesi in the period of March to July 2018. This research was arranged in a Randomized Block Design consisting of three treatments, namely (P1 = No trimming, P2 = Trimming 3 Lower Leaves, P3 = Trimming 5 Lower Leaves). The results indicated that lower leaves pruning on maize has no effect towards the diameter and length of cob, number of seeds per cob weighing to 1000 seeds, as well as the seed weight per cob. Lower leaves pruning is ineffective because assimilates sourced from the lower leaves are more focused on the development of plant roots. This is presumably due to the hybrid maize varieties, which has the capability to maintain the quality of the plants, therefore pruning 3 and 5 lower leaves has no significant effect towards the seed weight per cob and the weight of 1000 seeds. In this research the lower leaf trimming did not significantly affect the production of corn plants, but in the observation variables, the weight of 1000 seeds increased when compared to the weight of 1000 seeds in the description of pioneer varieties. The average weight of 1000 seeds in this research was on pruning the lower 3 leaves of 375.85 g while in pruning the lower 5 leaves 361.13 g and the weight of 1000 seeds in the description of pioneer varieties was 311 g, this meant an increase. Further research is required by considering the location of the leaves to be pruning.